EVALUATION OF WATERFRONT CITY TOURISM DEVELOPMENT DIRECTION AT TAMAN TERAS PARIT NANAS, NORTH PONTIANAK DISTRICT BASED ON THE 3A CONCEPT - Kurniawan, Ryan Rizky; Ulfa, Maria; Adlika, Nur Meily (GEOREFERENCE, 2025)
Waterfront City Taman Teras Parit Nanas is a tourism destination located along the banks of the Landak River. It was developed as part of an urban planning initiative and creative economic development strategy, focusing on the revitalization of riverbanks and surrounding residential areas. The purpose of this study is to analyze the application of the 3A tourism concept, which includes attractions, accessibility, and amenities. This research employs a qualitative approach with a descriptive research design. Data were collected through direct observation at the site, interviews with both managers and visitors, literature review of relevant regulations and legislation that support the development of the waterfront city, and GPS-based documentation to map elements related to the 3A tourism components. The findings reveal several critical issues, particularly in the suboptimal management of available facilities. Addressing these challenges requires effective collaboration among visitors, site managers, and the local community to enhance and realize the full tourism potential of Taman Teras Parit Nanas.